Karst geoheritage and geotourism potential in the Pek River lower basin (Eastern Serbia) - Antić, Aleksandar; Tomić, Nemanja; Marković, Slobodan (Geographica Pannonica, 2019)
Karst areas, as areas with attractive geological and geomorphological features are an important and integral part of geoheritage. They possess huge tourism potential and can be used for the development of geotourism. The Pek River basin is a highly dominant karst terrain with numerous geological and geomorphological features, especially caves. However, their geotourism potential still remains fully unrevealed. In this paper, we analyzed several geosites that represent significant karst geoheritage formations and as such they can be the backbone of future geotourism development in this area. The aim of this paper is to emphasize the geotourism potential of the Pek River lower basin and to determine the current state and geotourism potential of these geosites by applying the modified geosite assessment model (M-GAM).
Keywords: Pek; Karst; geotourism; geosites; geoheritage